Continued Exploration of Trifunctional Alkyl 4-Chloro-2-diazo-3-oxobutanoates: Streamlined Entry into [1,2,3]Triazolo[5,1-c][1,4]benzoxazines and [1,2,3]Triazolo[5,1-c][1,4]benzoxazepines - Budeev, Anton V.; Kantin, Grigory; Dar’in, Dmitry; Krasavin, Mikhail (Synthesis, 2021)
Further exploration of the trifunctional character of previously introduced alkyl 4-chloro-2-diazo-3-oxobutanoates in reactions with N-protected substituted o-aminophenols followed by deprotection provided a convenient entry into [1,2,3]triazolo[5,1-c][1,4]benzoxazines, which are of high medicinal importance, as documented in the literature. The same approach applied to N-protected substituted o-(aminomethyl)phenols afforded [1,2,3]triazolo[5,1-c][1,4]benzoxazepines, which are practically unexplored compounds from a medicinal chemistry perspective. The syntheses start with SN2-type alkylation of the phenol. Removal of the protecting group triggers imine formation followed by Wolff 1,2,3-triazole synthesis.
Keywords: diazo compounds; multicenter reactions; nucleophilic substitution; domino reactions; Wolff 1,2,3-triazole synthesis; benzoxazines; benzoxazepines